FACE VERIFICATION SYSTEM IN MOBILE DEVICES BY USING COGNITIVE SERVICES - Altun, Adem Alpaslan; Kolus, Cagatay (Prof. Dr. Ismail SARITAS, 2018)
Biometric systems enable people to distinguish between physical and behavioral characteristics. Face recognition systems, a type of biometric systems, use peoples’ facial features to recognize them. The aim of this study is to perform face recognition and verification system that can run on mobile devices. The developed application is based on comparing the faces in two photographs. The user uploads two photos to the system, the system identifies the faces in these photos and performs authentication between the two faces. As a result, the system gives the output that the two faces in the photo belong to the same or different persons. It provides a security measure thanks to the face identification and verification feature included in this application. This application can be integrated into various applications and used in systems such as user login.